ISLAMIC LAW AND BUGIS-MAKASSAR CULTURE: AN APPROACH TO ANTI-ILLEGAL GRATIFICATION - Marlina, Andi; Muliyono, Andi; Lahangatubun, Nurjanah (Jurnal Al-Dustur, 2024)
The objective concerning Anti-Illegal Gratification in the Perspective of Islamic Law and the Culture of Bugis-Makassar Community is to provide a profound understanding of the practice of illegal gratification within the Bugis-Makassar cultural context and Islamic legal perspective. This discussion also aims to provide a strong foundation for formulating effective prevention strategies related to illegal gratification. By exploring the perspectives of Islamic law and the culture of the Bugis-Makassar community, this discussion is expected to contribute positively to efforts to prevent illegal gratification and corruption in the Bugis-Makassar community, as well as to strengthen awareness of the importance of integrity and honesty in social interactions. This research employs a meticulous and in-depth literature review method, combining various reference sources. It is hoped that this research will provide a comprehensive understanding of the issue of illegal gratification from the perspectives of Islamic law and the culture of the Bugis-Makassar community. From the findings of this research, it can be concluded that efforts to prevent illegal gratification from the perspective of Islamic law and the culture of the Bugis-MakassarÂ community require a holistic approach that integrates local cultural values with Islamic legal principles. Concrete steps are needed to address existing challenges and strengthen social awareness of the importance of integrity and honesty in social interactions.